Changes in Eukaryotic and Bacterial Communities along a 120 m Transect Associated with a Shallow Marine Hydrothermal Vent - Rubelmann, Haydn; Karlen, David J.; Garey, James R. (Frontiers in Marine Science, 2017)
The biocomplexity of sediment communities along a 120 m transect near an arsenic-rich, shallow marine hydrothermal vent at Tutum Bay, Papua New Guinea was thoroughly examined. A count of macro- and meiofaunal organisms was combined with bacterial and eukaryotic SSU rRNA gene surveys to assess biodiversity. Each site along the transect had distinct microbial communities. Near-vent sites were more similar to each other than sites further from the vent. Some species, such as Ignavibacterium, Caldilinea, and Capitella were only found near-vent. Biodiversity generally increased with distance from the vent. The community composition responded to the presence of hydrothermal fluids with a clear correlation between temperature and thermophilic organisms. Primary production appeared to be a mix of chemo- and phototrophy. Association analyses suggest many potential interactions between organisms occur at certain sites, and that species distributions and interactions occur in the context of complex spatial relationships related to the geochemistry of the hydrothermal vent fluids. While Tutum Bay is heavily influenced by arsenic, no specific correlation between bacteria that metabolize arsenic and the concentration of different oxidation states of arsenic ions was observed, perhaps because very little of the arsenic present was bioavailable. The observed homogeneous distribution of arsenic reducers along the transect could be due to background arsenic metabolism. This study represents a holistic study of biocomplexity on a broad phylogenetic range across a 120m transect associated with a marine shallow-water hydrothermal vent.